Numerical Modelling of Laboratory Test of Plain Concrete Under Uniaxial Impact Compression - Adamczyk, R.; Łodygowski, T. (Engineering Transactions, 2003)
The aim of this study is to compare experimental results of the behaviour of concrete specimen, dynamically loaded in compression, carried out by P.H. BISCHOFF and S.H. PERRY [8], with the results obtained in numerical simulation. The intention of the investigation, re-ported in this paper, is to create the constitutive relation for concrete that depends on impact rates. The specimen was loaded in static as well as in dynamic tests. New constitutive relation of concrete dependent on impact rate has been proposed. Accuracy of the model was studied and compared with the experiment in simple σ – ε characteristics. Two cases of concrete strength 30 and 50 MPa and three initial impact rates were considered. After verification in a simple uniaxial test, the new constitutive relation has been applied in complex engineering problem. Numerical impact analysis was carried out for impact tests in the environment of the ABAQUS/Explicit finite element code, and ABAQUS/Standard for static tests [1].